Genetic Control of Enzyme Induction in the β-Ketoadipate Pathway of Pseudomonas putida: Two-Point Crosses with a Regulatory Mutant Strain - Wu, C.-H. (J Bacteriol, 1972)
Several mutant strains of Pseudomonas putida, selected on the basis of their inability to grow at the expense of benzoate, have been shown to be unable to form inducibly both muconate lactonizing enzyme and muconolactone isomerase. A secondary mutant strain derived from one of these pleiotropically negative strains forms these two enzymes and, in addition, catechol oxygenase in the absence of inducer. This constitutive mutant strain was used as a donor in transductionally mediated two-point crosses to determine the order of point mutations within the structural genes for muconate lactonizing enzyme and muconolactone isomerase (the catB and catC genes, respectively). The gene order conformed precisely with the one that has been established by deletion mapping.